Natural Mechanisms and Methods of Protection Against Coronavirus COVID-19 - Bryndin, Evgeny (Jour Med Resh and Health Sci, 2021)
Our planet is a living creature that has its own protective viral mechanism. Viruses are activated when people too zealously intervene in the natural processes on the planet and worsen the environment. With a decrease in the spiritual level of society, a deterioration in ecology, climate change, a decrease in the frequency of the Schumann resonator supporting the energy healthy state of the body, pollution of water and soil and other catastrophic disorders of natural processes on the planet, an epidemic and the process of mutation of viruses begins, as a result of which more and more of their species appear. For the people will rise against the people and the kingdom against the kingdom; and there will be earthquakes in places, and there will be smoothness and turmoil. This is the beginning of Mark's disease (13:8). The article discusses natural mechanisms and methods of protection against coronavirus.